Intrauterine Device Use and Cervical Cancer Risk: A Systematic Review and Meta-analysis. Issue 6 (December 2017) - Cortessis, Victoria K.; Barrett, Malcolm; Brown Wade, Niquelle; Enebish, Temuulen; Perrigo, Judith L.; Tobin, Jessica; Zhong, Charlie; Zink, Jennifer; Isiaka, Vanessa; Muderspach, Laila I.; Natavio, Melissa; McKean-Cowdin, Roberta
Abstract : OBJECTIVE: To estimate the association between use of an intrauterine device (IUD) and risk of cervical cancer by subjecting existing data to critical review, quantitative synthesis, and interpretation. DATA SOURCES: We searched PubMed, Web of Science, ClinicalTrials.gov, and catalogs of scientific meetings and abstracts, theses, and dissertations queried from inception through July 2016. METHODS OF STUDY SELECTION: Examination of abstracts from 225 reports identified 34 studies with individual-level measures of use of an IUD and incident cervical cancer. By critically assessing the full text of these reports, independent reviewers identified 17 studies conducted without recognized sources of systematic error, of which 16 could be harmonized for meta-analysis. TABULATION, INTEGRATION, AND RESULTS: Point and interval estimates of the association between use of an IUD and incident cervical cancer were extracted from original reports into a structured database along with key features of study design and implementation. A random-effects meta-analysis was implemented to quantitatively synthesize extracted estimates and assess likely influence of publication bias, residual confounding, heterogeneity of true effect size, and human papillomavirus prevalence and cervical cancer incidence in source populations. Women who used an IUD experienced less cervical cancer (summary odds ratio 0.64, 95% CI 0.53–0.77). Neither confounding by recognized risk factors nor publication bias seems a plausible explanation for the apparent protective effect, which may be stronger in populations with higher cervical cancer incidence. CONCLUSION: Invasive cervical cancer may be approximately one third less frequent in women who have used an IUD. This possible noncontraceptive benefit could be most beneficial in populations with severely limited access to screening and concomitantly high cervical cancer incidence. Abstract : Women who have used an intrauterine device are diagnosed with cervical cancer approximately one third less frequently than others.